DESIGN AND IMPLEMENTATION OF EDUCATIONAL TECHNOLOGIES ON ROBOTICS - Mukhamediyeva, К.М.; Mukhamediyeva, Г.Ш.; Abisheva, И.Ш. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The formation of digital transformation is a objective for Kazakhstani universities at the highest strategic level. An important problem is the widespread training of teachers to conduct basic and additional classes in robotics in schools, colleges and universities. The education system has a clear need for teachers who are proficient in appropriate teaching methods at a high level. The purpose of this article was to study the approach to designing educational technology (ET) in robotics, which allows organizing educational activities in robotics to ensure the achievement of learning outcomes, which is what our study is devoted to. We see the solution to these problems in the need to develop a functional model for the design of educational technology in robotics. The process of interaction between the educational process subjects involved in the formation of activity-oriented professionalism in robotics has led to the organization a digital environment, which is a prerequisite for the effective design of ET in robotics utilizing digital technologies.